Future of Futures Research: Trends and Challenges in Communication Studies - Abu Hassan Hasbullah (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2009)
This paper examines future studies as an approach to better understand future possibilities in order to make better decisions today. Like historical studies that try to explain what happened in the past and why, the efforts of futures studies try to understand the latent potential of the present. Future studies and communication normally merging the facing of cultural diversity under globalization conditions, and the future research of futures communication sided the emergence of forecasting and foreseeing, extrapolation of creativity and innovation in shaping future. Keywords: future studies, communication studies